A research on defect image enhancement based on partial differential equation of quantum mechanics. (2018) - Wang, Zhonghua; Wang, Feiwen; Chi, Guiying
The defect image enhancement of aeronautic component is vital for the defect quantitative and qualitative properties. In this paper, a novel defect image enhancement algorithm is presented, which adopts the partial differential equation of quantum mechanics. The algorithm includes two key steps as follows. Firstly, according to the quantum mechanics theory, the image edge quantum probability is computed. Secondly, the partial differential equation coupling the anisotropic edge quantum probability is constructed to enhance the defect images of aeronautical component. Compared with other methods, the experimental results indicate that the proposed method better highlight the defect images.